A WEAK GRAVITATIONAL KNOT IN (2+1)-DIMENSIONAL EMPTY SPACE-TIME - Hadi, Miftachul; Muliyono, Suhadi (Universitas Mataram, 2025)
We propose the existence of a topological object, a weak gravitational knot, in the framework of an Abelian Chern-Simons action with a small positive cosmological constant in (2+1)-dimensional empty space-time.